DETERMINATION OF THE GROUP AFFILIATION OF HUMAN HAIR IN FORENSIC BIOLOGICAL PRACTICE - Mukharrama A. Khasanova; Akobir R. Nurov; Xayotbek V. Nurmatov; Nilufar D. Ashurova; Zumrad A. Muxitdinova (Central Asian Journal of Medicine, 2024)
The results of the study showed that the extracts of grape seeds “Nimrang” and “Saphora Japonica L” can be used as hemagglutination drugs (anti-A and anti-B phytagglutinin) for the detection of antigens A and B in blood stains. The use of phytagglutinins is more economical than the use of expensive heteroimmune and isohemagglutinating serums in the detection of antigens A and B in blood stains during the examination of physical evidence. Detection of antigens A,B0(H) in hair by methods of absorption of agglutinins in quantitative modification, absorption-elution and affinity chromatography are more reliable and selected methods in expert practice for the study of physical evidence.